Data: Hydrodynamics (Reynolds number) determine scaling, nucleation and crystal growth kinetics in membrane distillation crystallisation - McAdam, Ewan; Jikazana, Aphiwe; Campo Moreno, Pablo (Cranfield University, 2023)
Dataset for journal article "Hydrodynamics (Reynolds number) determine scaling, nucleation and crystal growth kinetics in membrane distillation crystallisation"
Keywords: membrane distillation experiments'; 'membrane crystallisation'